Timescape : saving Shakespeare [games] : an escape room game. (Ridley's Games, 2023)
"The fate of the world's greatest playwright rests in your hands! Travel back to Elizabethan England to save William Shakespeare from a sinister plot that has him locked up for a crime he did not commit. Worse still, it could destroy his reputation. This immersive escape room game challenges you and your friends to rescue the bard and his works. Test your skill, logic, cunning, and teamwork as you work together to decode the clues and uncover the truth".